Living in a Nanotech Home: Invisibility, Representation and Democratic Oversight of Nanotechnological Developments. - de Cózar-Escalante, José Manuel (Techné: Research in Philosophy & Technology)
While applying general ethical principles and reasoning to the dilemmas presented by the development of nanotechnology is often useful and always legitimate, we also need to find a way to bridge the gap between general principles and the specific issues that arise from the development of individual nanotechnologies. Drawing inspiration from pragmatist thinking, a useful strategy is to focus on the links between the epistemological, political and social representations of a particular case. Using the example of a nanotechnological house, this paper analyzes the problematic connections between scientific knowledge, technical expertise, decisionmaking and public engagement in nanotechnology representational networks.